Teaching Compassion in the Machine Age: Islamic Pedagogy, Artificial Intelligence, and the Formation of Ethical Citizenship in a Fragmented World - Ismail, Zhang; Nurteti, Lilis (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2026)
Artificial intelligence increasingly shapes educational experiences and social interactions worldwide. Its expansion creates opportunities and ethical challenges for citizenship formation. Contemporary societies face fragmentation, polarization, exclusion, and declining social trust. These conditions require educational approaches grounded in compassion and moral responsibility. This article explores Islamic pedagogy as a framework for ethical citizenship. It employs a conceptual and critical review of relevant literature. The analysis examines Islamic educational values alongside emerging AI technologies. Particular attention is given to compassion, justice, empathy, and social solidarity. Findings suggest that Islamic pedagogy offers important ethical guidance. These values can humanize technology-mediated learning environments. They also counter tendencies toward dehumanization and social isolation. Furthermore, compassionate education strengthens civic responsibility in diverse societies. AI should support, not replace, ethical human development. The study proposes integrating Islamic ethical principles into AI-enhanced education. This integration contributes to inclusive, responsible, and compassionate citizenship formation.